Analysis of electric machinery and drive systems - Krause, Paul C; Wasynczuk, Oleg; Sudhoff, Scott D; Pekarek, Steven; IEEE Xplore (Online Service); Wiley; Institute of Electrical and Electronics Engineers (Hoboken, New Jersey : Wiley, 2013)
Introducing a new edition of the popular reference on machine analysisNow in a fully revised and expanded edition, this widely used reference on machine analysis boasts many changes designed to address the varied needs of engineers in the electric machinery, electric drives, and electric power industries. The authors draw on their own extensive research efforts, bringing all topics up to date and outlining a variety of new approaches they have developed over the past decade.Focusing on reference frame theory that has been at the core of this work since the first edition, this volume goes a step further, introducing new material relevant to machine design along with numerous techniques for making the derivation of equations more direct and easy to use.Coverage includes:. Completely new chapters on winding functions and machine design that add a significant dimension not found in any other text. A new formulation of machine equations for improving analysis and modeling of machines coupled to power electronic circuits. Simplified techniques throughout, from the derivation of torque equations and synchronous machine analysis to the analysis of unbalanced operation. A unique generalized approach to machine parameters identificationA first-rate resource for engineers wishing to master cutting-edge techniques for machine analysis, Analysis of Electric Machinery and Drive Systems is also a highly useful guide for students in the field.
Index 636.
"Institute of Electrical and Electronics Engineers."
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/22/2015.
Keywords: Electric machinery; Electronic books